2005
DOI: 10.1590/s1516-89132005000500003
|View full text |Cite
|
Sign up to set email alerts
|

Thermal requirements of Trichogramma pretiosum and T. acacioi (Hym.: Trichogrammatidae), parasitoids of the avocado defoliator Nipteria panacea (Lep.: Geometridae), in eggs of two alternative hosts

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
2
10
0
4
Order By: Relevance
“…2). Longer longevity of T. pretiosum (22 days) and T. acacioi (8 days) at temperature similar to their thermal inferior limits confirmed the reports of these species being collected at altitudes near 1.000 m. However, T. pretiosum presented an inverse relationship between longevity and temperature increase which indicated that the effect of this parameter varied with Trichogramma species (Maceda et al 2003;Pratissoli et al, 2004b;Pratissoli et al, 2005b). Parasitism potential of T. pretiosum was also found to be directly related to the lineage of this parasitoid and to the host and weather conditions (Inoue and Parra, 1998;Faria et al, 2000;Pratissoli and Parra, 2000;2001;Pratissoli et al, 2004b Means followed by the same letter, in each column, do not differ between themselves by the test of Tukey at 5% probability level.…”
Section: Resultssupporting
confidence: 55%
“…2). Longer longevity of T. pretiosum (22 days) and T. acacioi (8 days) at temperature similar to their thermal inferior limits confirmed the reports of these species being collected at altitudes near 1.000 m. However, T. pretiosum presented an inverse relationship between longevity and temperature increase which indicated that the effect of this parameter varied with Trichogramma species (Maceda et al 2003;Pratissoli et al, 2004b;Pratissoli et al, 2005b). Parasitism potential of T. pretiosum was also found to be directly related to the lineage of this parasitoid and to the host and weather conditions (Inoue and Parra, 1998;Faria et al, 2000;Pratissoli and Parra, 2000;2001;Pratissoli et al, 2004b Means followed by the same letter, in each column, do not differ between themselves by the test of Tukey at 5% probability level.…”
Section: Resultssupporting
confidence: 55%
“…Biological control is a key component of integrated pest management programs as an alternative to pesticides, but knowledge on interactions between natural enemies, hosts and abiotic factors is required to optimally select biological control agents (Pratissoli et al 2005Desneux et al 2010;Ragsdale et al 2011). Natural parasitism of lepidopteran pests by Trichogramma (Hymenoptera: Trichogrammatidae) in Brazilian cotton fields suggested the possibility to use these parasitoids as biological control agents against H. virescens in cotton.…”
Section: Introductionmentioning
confidence: 99%
“…Trichogramma spp. are successfully used in biological control of various lepidopteran agricultural pests (Smith 1996;Pratissoli et al 2005;Desneux et al 2010;Suckling and Brockerhoff 2010). Trichogramma spp.…”
Section: Introductionmentioning
confidence: 99%
“…The mass rearing of this parasitoid in Sitotroga cerealella (Olivier) (Lepidoptera: Gelechidae) or Anagasta kuehniella (Zeller) (Lepidoptera: Pyralidae) eggs has allowed its use in programs of IPM (Parra, 1997;Pratissoli et al, 2005b). On other hand, pesticides may limit the efficiency of biological control agents.…”
Section: Introductionmentioning
confidence: 99%